SEMICLASSICAL MOSER-TRUDINGER INEQUALITIES - Arora R.; Nam P.T.; Nguyen P.-T. (My University, 2025)
We extend the Moser-Trudinger inequality of one function to systems of orthogonal functions. Our results are asymptotically sharp when applied to the collective behavior of eigenfunctions of Schrödinger operators on bounded domains. © 2024 American Mathematical Society. All rights reserved.